Complex reactive event processing for assisted living: The Habitat project case study. (15th July 2019) - Loreti, Daniela; Chesani, Federico; Mello, Paola; Roffia, Luca; Antoniazzi, Francesco; Cinotti, Tullio Salmon; Paolini, Giacomo; Masotti, Diego; Costanzo, Alessandra
Highlights: The backbone infrastructure of an assisted living system for elderly is presented. Smart object's interoperability is realized through a semantic message routing engine. The decision support system combines Complex Event Processing and Event Calculus. The adopted approach simplifies the formulation of temporal properties. A practical overview of some relevant real-world scenarios is provided. Abstract: While the increasing average age of population is posing new challenges to societies and healthcare systems, the emergence of the Internet of Things research area is generating the hope for automated assisted environments, which could combine the advances in sensors networks with that of runtime monitoring systems, in order to create smart houses able to take care of their older inhabitants and delay the recourse to hospitals and nursing homes. However, although various assisted living systems have been proposed in the last decade, the goal of realizing an effective domestic support system for elderly is still far from reached. In this work, we present a project aiming to re-engineer a set of everyday life objects, equipping them with environmental and wearable sensors, thus to monitor the condition of older people in their domestic residences and provide security while preserving the autonomy and independence of the subjects. The main focus of the paper at hand is on the requirements and solutions implemented to realize the backbone infrastructure of such system as regards both the adopted semantic message routing mechanism and the newly conceived approach to event analysis, which combines Complex Event Processing and a reactive implementation of Event Calculus.